The Impact of Korean Wave on South Korea's Export of Consumer Goods to ASEAN-5 Country - Tandy, Alyssa Chiara Handini; Handoyo, Rossanto Dwi (Journal of Developing Economies, 2024)
This study aims to assess the impact of the Korean Wave on the export of consumer goods from South Korea to the ASEAN-5 countries (Indonesia, Malaysia, Thailand, Singapore, and the Philippines) from 2010 to 2020. This study took into account various factors to analyze the export dynamics, such as gross domestic product (GDP) per capita, interest rates, Google search trends, and the geographical distance between countries. Cultural goods exported from South Korea were used as a measure of the Korean Wave, employing the gravity model and the fixed effects model (FEM) for analysis. The results of this study indicated a positive impact of the Korean Wave variable on the export of South Korean consumer goods. Additionally, the findings revealed that variables such as South Korea's GDP per capita, distance, and exchange rates had a negative impact on the export of such goods. Furthermore, this study highlights the positive impacts of the ASEAN-5 countries' GDP per capita and Google search trends on the export of South Korean consumer goods.